The dual Function Two Highly Robust Estimators Of Scale. - S.S., Syed Yahaya; A.R., Othman; H.J., Keselman (2006)
Two statistics for testing the equality of central tendency measures under conditions of variance heterogeneity and non-normality, i.e. S1 and MOM-H, were compared in the context of a one-way completely randomized design.